SCHOOL HEALTH IN VOCATIONAL EDUCATION SPECIALIST PHYSICAL EDUCATION - Lubov Vladimirovna Belova; Alexander Konstantinovich Belov (Вестник Северо-Кавказского федерального университета, 2022)
The paper presents an analysis of the priority directions of modernization of vocational training in the field of physical culture in the context of health-technology identified possible areas of its optimization from the perspective of a competent approach.